Understanding the Relationship Between Debt Financing and Income Inequality in South Asia (Journal of Asian Development Studies, 2021)
This study examines the relationship between debt and inequality in a penal of seven South Asian economies over the period from 1996 to 2014. The study incorporated domestic debt, external debt and debt servicing as debt measures in a single penal model. The control variables are government effectiveness, GDP and trade openness. The study used Least Square Dummy Variable (LSDV) Fixed Effect model, Pooled OLS and Random Effect model with standard diagnostics of Hausman test, Langragian Multiplier test and F-test for model efficiency. The econometric analysis is also supported by standard diagnostic test for serial autocorrelation, heteroskdasticity and multicolinearity. The empirical results of random effect model in the study indicate that debt servicing; domestic debt and external debt are negatively and significantly affecting inequality in south Asia. The study concludes that along with other traditional factors increase in debt indictors are significant in redistributing the income among the public and decrease the inequality. The study suggested that there is need of balanced and effective mechanism to make use of policies regarding debt factors.